Tumor-Associated Macrophages in Canine Oral and Cutaneous Melanomas and Melanocytomas: Phenotypic and Prognostic Assessment - Porcellato, Ilaria; Sforna, Monica; Lo Giudice, Adriana; Bossi, Ilaria; Musi, Alice; Tognoloni, Alessia; Chiaradia, Elisabetta; Mechelli, Luca; Brachelente, Chiara (Frontiers in Veterinary Science, 2022)
The tumor microenvironment is a complex system, where neoplastic cells interact with immune and stromal cells. Tumor-associated macrophages (TAMs) are considered among the most numerically and biologically noteworthy cellular components in tumors and the attention on this cellular population has been growing during the last decade, both for its prognostic role and as a potential future therapeutic target. Melanoma, particularly the oral form, despite being one of the most immunogenic tumors, bears a poor prognosis in dogs and humans, due to its highly aggressive biological behavior and limited therapeutic options. The aims of this study are to characterize and quantify TAMs (using CD163, CD204, Iba1, and MAC387) in canine melanocytic tumors and to evaluate the association of these markers with diagnosis, histologic prognostic features, presence of metastases, and outcome, and to provide preliminary data for possible future therapies targeting TAMs. Seventy-two melanocytic tumors (27 oral melanomas, 25 cutaneous melanomas, 14 cutaneous melanocytomas, and 6 oral melanocytomas) were retrospectively selected and submitted to immunohistochemistry and double immunofluorescence. Double immunolabeling revealed that most CD163+ and CD204+cells co-expressed Iba1, which labeled also dendritic cells. Iba1 was instead rarely co-expressed with MAC387. Nevertheless, the expression of macrophagic markers showed a mild to moderate association among the four markers, except for CD204 and MAC387. The number of CD163+, CD204+, and MAC387+ cells was significantly higher in oral melanomas compared to oral melanocytomas (p<0.001; p<0,05 and p<0.01, respectively), whereas Iba1 was differentially expressed in cutaneous melanomas and melanocytomas (p<0.05). Moreover, CD163, IBA1 and MAC387 expression was associated with nuclear atypia and mitotic count. The number of CD163+cells was associated with the presence of metastases and tumor-related death in oral melanocytic tumors (p<0.05 and p=0.001, respectively).